Discourses of social media amongst youth: An ethnographic perspective. (August 2022) - Ilbury, Christian
Abstract: Recent large-scale surveys of social media have repeatedly shown that Facebook and Twitter are losing popularity amongst teenagers, with newer 'image-first' apps such as Snapchat and Instagram becoming preferred amongst this demographic. Whilst there is a wealth of research which has examined more general reasons for this shift, it is unclear to what extent these explanations can account for more local level user practices. This article interrogates these issues by taking an ethnographic approach to examine prevalent discourses of social media amongst young people in an East London youth group. Specifically, I explore the ways in which social media apps and platforms are discursively represented by the young people with reference to their everyday lives. This leads me to argue that whilst some of their practices can be accounted for by broader trends of social media use, issues that reflect the lived realities of the young people (e.g., crime, social networks) equally influence their engagements with different platforms.